Techno‐economic assessment of nonfossil ammonia production. Issue 4 (4th November 2013) - Tunå, Per; Hulteberg, Christian; Ahlgren, Serina
<x xml:space="preserve">Abstract</x> The production of nitrogen fertilizers are almost exclusively based on fossil feedstocks such as natural gas and coal. Nitrogen fertilizers are a necessity to maintain the high agricultural production that the world's population currently demands. Ammonia produced from nonfossil‐based feedstocks would enable renewable production of ammonia. Renewable feedstocks are one thing, but perhaps even more important in the future are the security of supply that decentralized production enables. In this study, the techno‐economic evaluation of production of ammonia from various renewable feedstocks and for several plant sizes was investigated. The feedstocks included in this study are grid‐based electricity produced from wind power, biogas, and woody biomass. The feedstocks differed in exergy, and to make a fair comparison, the electric equivalence ratios method was used. The results showed that the energy consumption for biogas and electricity is the same at 42 GJ/tonne ammonia. When using the electric equivalence comparison for the same cases, the results are 26 and 42 GJ/tonne, respectively. Biomass‐based production has an energy consumption of 58 GJ/tonne and 31 GJ/tonne when using the electric equivalence comparison, which should be compared with the industrial average of 37 GJ (or 21 GJ electric equivalence) per tonne of ammonia. Monte Carlo simulations were used to vary the inputs to the process to evaluate the production cost. The ammonia production cost ranged from $680 to 2300/tonne ammonia for the various cases studied. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 1290–1297, 2014